2008
DOI: 10.1002/app.28563
|View full text |Cite
|
Sign up to set email alerts
|

Durability of the wettability properties of a polypropylene film with a low‐pressure CH4–O2 plasma treatment

Abstract: The aim of this work was to study the durability of a polypropylene film plasma-treated with an 80 : 20 methane-oxygen gas mixture. Three different storage conditions were used to evaluate the influence of the relative humidity and temperature on the aging process. The surface functionalization of the polypropylene film was analyzed with X-ray photoelectron spectroscopy and attenuated total reflectance/Fourier transform infrared spectroscopy analysis, and the variations of the surface energy and its polar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Therefore, the use of slow distances nozzle-surface of LDPE sheets and treatment rate is suitable to promote a more pronounced increase in surface wettability. Finally, as we can observe in Figure 2, In general it is observed that the surface modification of LDPE sheets through the application of atmospheric plasma is due to insertion of polar groups and allows optimal functionalization of the polymer surface at low treatment rate and nozzle-surface distance 29,30 .…”
Section: (Figure 2)mentioning
confidence: 82%
“…Therefore, the use of slow distances nozzle-surface of LDPE sheets and treatment rate is suitable to promote a more pronounced increase in surface wettability. Finally, as we can observe in Figure 2, In general it is observed that the surface modification of LDPE sheets through the application of atmospheric plasma is due to insertion of polar groups and allows optimal functionalization of the polymer surface at low treatment rate and nozzle-surface distance 29,30 .…”
Section: (Figure 2)mentioning
confidence: 82%
“…They realized that before treatment the polymer was wrinkled, with cracks that tended to disappear after treatment with CH 4 , indicating an effect of smoothing by exposure to plasma. Garcia et al (2008) 13 reported identify the deposition of an organic material rich in oxygen on the surface of polypropylene (PP), when treated with RF plasma in methane-oxygen mixture (80:20) at a power of 150 W. The authors studied the surface energy of the treated PP and obtained lower values of dispersive component, indicating a low attack effect of the gaseous mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that active species generated during the action of the plasma remained on the surface of the material and reacted with oxygen in the air after treatment, forming polar groups. Garcia et al (2008) 13 when studying plasma treatment of PP in an atmosphere of CH 4 :O 2 (8:2), also identified an increase in the O/C ratio, of 0.04 for 0.13 after 60 s treatment. According to these authors, the use of plasma containing an organic monomer such as methane is known as plasma polymerization, resulting in the deposition of organic material on the substrate.…”
Section: Measurement Of Water Absorption Ratementioning
confidence: 94%
“…8,9 In addition, the substrate surfaces modified by the grafting technique can be durably retained. Conversely, while hydrophilic properties gradually regress by turnover or migration of polar functional groups generated, when the surfaces were modified by plasma treatment 10,11 or UV irradiation. [12][13][14] We have studied surface modification of the LDPE, HDPE, and PP plates by the photografting technique for more than a decade.…”
Section: Introductionmentioning
confidence: 99%